RICOSRE-Assisted Learning with Podcasts in Biology Education: Enhancing Analytical Thinking and Communication Skills - Nukhbatul Bidayati Haka; Lilis Kusuma Sari; Supriyadi; Akbar Handoko; Nur Hidayah; Hardiyansyah Masya (Sagamedia Teknologi Nusantara, 2023)
In the 21st century, digital technology has rapidly advanced, with the general population commonly possessing devices such as smartphones, laptops, or computers at home. Podcasts offer advantages in terms of time efficiency and multitasking, allowing learners to engage in educational content while engaged in various activities such as commuting, writing, working, and more. This research utilizes the RICOSRE learning model with Podcasts to investigate its impact on students’ analytical thinking and communication skills in biology. The study employs a quantitative approach, precisely the quasi-experimental method, to assess the influence of the RICOSRE learning model, supported by podcasts, on students’ analytical thinking and communication skills in biology. Data collection involves pretests, posttests, and observation sheets. The research findings demonstrate a positive impact of the RICOSRE learning model. The experimental group outperformed the control group in analytical thinking ability, with an average percentage of 2.90% compared to 1.85%. Communication skills observation sheets show an average percentage of 76.91% for the experimental group and 59.44% for the control group. These findings confirm the effectiveness of the RICOSRE learning model in enhancing students’ analytical thinking and communication skills in biology education.